Challenges in Development TEVT Leadership in Malaysia - Norhaidi Nordin; Muhammad Faizal A. Ghani (The Faculty of Education and Teaching Training, 2022)
Currently, Malaysia has 88 Vocational Colleges, which mainly offer programs in the field of Technical and Vocational Education and Training (TVET). It implies that leaders will have various behaviors in leading Vocational Colleges to enhance student learning. Consequently, developing a quality leadership style among Vocational College leaders would be difficult. Thus, this article explores the challenges of developing TVET leadership among Vocational College leaders. A qualitative method was implemented to collect data through face-to-face interviews among six Vocational College leaders. The data were analyzed using thematic analysis methods. The findings of this study reported that the challenges to developing a quality leadership style among Vocational College leaders are as follows: (a) negative attitude of leaders, (b) lack of leadership competence, (c) rapidly changing educational policies, (d) formation of organizational structure less adherence to the TVET's vision, (e) less control over leader behavior, (f) less collaborative among stakeholders and (g) leaders who are less concerned with diversity factors. The findings of this study can make stakeholders, especially policymakers and leaders of Vocational Colleges, aware of the need to identify the cause of an issue for resolution. Saat ini, Malaysia memiliki 88 Sekolah Kejuruan, yang sebagian besar menawarkan program di bidang Pendidikan dan Pelatihan Teknik dan Kejuruan (TVET). Ini menyiratkan bahwa akan ada keragaman perilaku di antara para pemimpin Sekolah Kejuruan untuk meningkatkan pembelajaran siswa. Dengan demikian akan sulit untuk mengembangkan gaya kepemimpinan yang berkualitas di antara para pemimpin Sekolah Menengah Kejuruan. Oleh karena itu, artikel ini bertujuan untuk mengeksplorasi tantangan dalam mengembangkan kepemimpinan TVET di kalangan pimpinan Sekolah Kejuruan. Metode kualitatif digunakan untuk mengumpulkan data melalui wawancara tatap muka antara enam pimpinan Sekolah Menengah Kejuruan. Analisis data menggunakan metode analisis tematik. Temuan penelitian melaporkan bahwa tantangan untuk mengembangkan kualitas gaya kepemimpinan di kalangan pemimpin Sekolah Kejuruan adalah sebagai berikut: (a) sikap negatif pemimpin, (b) kurangnya kompetensi kepemimpinan, (c) kebijakan pendidikan yang selalu berubah, (d) pembentukan struktur organisasi yang kurang sesuai dengan visi TVET, (e) kurang mengontrol perilaku pemimpin, (f) kurang kolaboratif antar pemangku kepentingan, dan (g) pemimpin kurang peduli dengan faktor keragaman. Temuan penelitian ini diharapkan dapat memberikan kontribusi kepada para pemangku kepentingan, khususnya pengambil kebijakan dan pimpinan Sekolah Kejuruan tentang perlunya mengidentifikasi akar permasalahan kepemimpinan untuk tujuan pemecahannya.